PARTISIPASI MASYARAKAT DALAM PENGELOLAAN OBJEK WISATA SUMBER UMBULAN DI DESA NGENEP, KECAMATAN KARANG PLOSO, KABUPATEN MALANG - Teturan, Alfonsina; Ba'diya Kusufa, Roni Alim; Meviana, Ika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the phenomenon of community participation in community-based tourism (CBT) development in Ngenep Village, Malang Regency. The primary objective of this study is to describe and analyze forms of community participation and to identify supporting and inhibiting factors in the management of the Sumber Umbulan tourist site. This study employs a descriptive qualitative approach. Data were collected through direct field observations, in-depth interviews with key informants (the village head, tourism managers, and local residents), and a review of documents. The research findings indicate that: (1) Forms of community participation in Ngenep Village encompass four main dimensions: intellectual participation (ideas/concepts in planning), labor participation (mutual aid and facility improvements), skill-based participation (management training), and material participation in the form of monetary contributions and assets (work equipment). The community positions itself as the driving force throughout the planning to evaluation stages, coordinated with the managers. (2) Factors supporting participation include natural resource potential (pristine springs), awareness of the benefits of the circular economy, and strong cultural values and traditions (such as the Malam 1 Suro ritual) that foster a sense of ownership. (3) The main inhibiting factors consist of limited financial capital for facility expansion and limitations in the quality of human resources (HR) in